Axillary cutaneous metastasis of colon cancer with microsatellite instability-high and BRAF V600E mutation treated with curative-intent surgery: a case report - Daisuke Yamai; Yoshifumi Shimada; Hikaru Ozeki; Akio Matsumoto; Kaoru Abe; Yosuke Tajima; Mae Nakano; Hiroshi Ichikawa; Jun Sakata; Toshifumi Wakai (Surgical Case Reports)
Abstract Background Colorectal cancer (CRC) metastasizes to various organs, while cutaneous metastases are rare. Although there have been several previous reports of axillary cutaneous metastases with other metastases of CRC, there has never been a report of axillary cutaneous metastasis of CRC that could be treated with curative-intent surgery. Case presentation A 68-year-old female was diagnosed with an axillary cutaneous tumor and ascending colon cancer with invasion to the duodenum. Histopathological and immunohistochemical analysis revealed that the axillary cutaneous tumor showed adenocarcinoma and the same expression pattern for cytokeratin 7, cytokeratin 20, and CDX2 as the ascending colon cancer, and that proved to be KRAS–NRAS wild type, MSI-H, and with a BRAF V600E mutation. The patient underwent a two-stage resection with curative intent after receiving neoadjuvant chemotherapy which consisted of one cycle of modified FOLFOX6 followed by two cycles of FOLFOXIRI. During and after the two operations, the patient received a total of nine cycles of modified FOLFOX6 as adjuvant chemotherapy. Two years after the initial surgery, and 1 year and 8 months after the second surgery, the patient is alive without recurrence. Conclusions To the best of our knowledge, this is the first report of axillary cutaneous metastasis of CRC with microsatellite instability-high and BRAF V600E mutation that could be treated with curative-intent surgery. It is important to recognize the presence of such cases for the accurate diagnosis and treatment of CRC with cutaneous metastasis.